Analisis Dampak Kecanduan Judi Online (Slot) Terhadap Keharmonisan Keluarga : Studi Kasus Kepala Keluarga Desa Bunga Tanjung - Arifina, Dhea Astri; Yusnadi, Yusnadi; Takwin, Muhammad (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2024)
The purpose of this study was to analyze the impact of online gambling addiction (slots) on family harmony. The research was conducted using a qualitative case study approach, five heads of households in Bunga Tanjung Village, known to experience online slot gambling addiction, were examined. The results showed that the higher the online game addiction among family members, the greater the negative impact on family harmony. The main impact includes reduced interaction and communication within the family, loss of the head-of the family’s role, development of long-term conflicts, and damage to family welfare. The study concludes that online gambling addiction has a significant impact on decreasing the quality of family harmony. Solutions include the prevention and treatment efforts through socialization, counseling, rehabilitation, and social support to aid affected families to recover